The role of financial and marketing services on rural shea-producing women - Chakilia, Safianu; Ahado, Hillary Edinam (Goodwood Publishing, 2024)
Purpose: This study aims to empirically investigate the impact of financial and marketing services on shea butter production, with an emphasis on the Tolon district of Ghana, to inform evidence-based policies and practices. Research methodology: This study employed a quantitative research design, utilizing a survey approach to collect data from a sample of shea butter producers in the Tolon District of Ghana. In total, 151 Shea nut processors from Tolon, Dimabi 1, and Dimabi 2 were selected using a combination of purposive and simple random sampling techniques. Data were collected through structured questionnaires, which were subsequently analyzed using quantitative methods. Furthermore, the study employed linear regression analysis with an endogenous treatment effect model in STATA version 17 to examine the relationship between financial and marketing services, and shea butter production. Results: The empirical evidence derived from the linear regression with the endogenous treatment model indicates a statistically significant and positive relationship between financial and marketing services and shea butter production, indicating that financial and marketing services are significant factors in predicting the productivity of shea butter production. Limitations: The sample size of the study was small, which may restrict the generalizability of the findings. Contribution: This study provides novel insights into the dynamics of shea butter production in Ghana’s Tolon District by highlighting the quantitative effect of financial and marketing services on shea butter production, and the importance of improving access to these services. This study also provides evidence-based recommendations for collaborative synergies between government and non-governmental organizations to establish microfinance programs and marketing service centers to facilitate easier access to these essential services for shea butter producers.